"Na Gorącym Uczynku" - "antyalkoholowy" kryminał Władysława Sabowskiego = "Caught Red-Handed" - Władysław Sabowski's "anti-alcoholic" detective story - Narolska, Aneta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an analysis and interpretation of the novel by Władysław Sabowski "Caught Red-handed.A Page from Criminal Records", published in "Home Carer" in 1868. The novel is discussed as an example of a popular novel, which combines the convention of crime novel (detective and courtroom) with the novel of mystery in the style of Eugene Sue and which is enriched with moralistic elements.
Keywords: Sabowski, Władysław (1837-1888); literatura polska - 19 w. - tematyka; powieść kryminalna